So I'm trying to do this problem where I'm given the Lagrangian density for a piano string which can vibrate both transversely and longitudinally. $\eta(x,t)$ is the transverse displacement and $\xi(x,t)$ is the longitudinal one. (So a point at $[x,0]$ at some later time t would be at $[x+\xi(x,t),\eta(x,t)]$). The Lagrangian density is given by $$\mathcal{L} = \frac{\rho_0}{2}[\ddot{\xi}^2+\ddot{\eta}^2]-\frac{\lambda}{2}[\frac{\tau_0}{2}+\xi'+\frac{1}{2}(\eta')^2]^2$$ where the dot is a partial time derivative and a prime is a partial x derivative. Also $\lambda$, $\tau_0$ and $\rho_0$ are parameters such as the Young's modulus, density and tension of the string respectively. So applying the action principle in the case of a continuous system I get the following PDEs for $\xi$ and $\eta$: $$\ddot{\xi} = \frac{\lambda}{\rho_0}(\xi''+\eta'\eta'')$$ and $$\ddot{\eta} = \frac{\lambda}{\rho_0}[\eta''(\frac{\tau_0}{\lambda} + \xi'+\frac{3}{2}(\eta')^2)+\eta'\xi'']$$.

Linearization of the equations yields two simple wave equations, the $\eta$ wave traveling at a speed $c_T^2 = \frac{\tau_0}{\rho_0}$ and the $\xi$ wave at $c_L^2 = \frac{\lambda}{\rho_0}$.

Now the part that is stumping me is that the problem asks us to show that if a given pulse of the form $\eta(x,t) = \eta(x-c_Tt)$ propagates along the string then that induces a concurrent longitudinal pulse of the form $\xi(x-c_Tt)$. Obviously I can't use the linearized equations to prove this. I would have to use some sort of iterative process by using exact PDE's to get the next step. But I tried doing this and I just get a mess. Any ideas where to go from here? (for reference this is problem 1.10 in Stone and Goldbart's book).

  • $\begingroup$ Take you first EOM and use method of Fourier transform. Expand $\xi$ in terms of $exp(ikx)$ (coeff. will then depend on t and k) and expand $\eta'\eta''$ in terms of $exp(ik(x-c_Tt))$ (coefficients here will only depend on k). Then for each k you will get equation for a forced harmonic oscillator whose solution will necessarily consist of frequency imposed on it by forcing term. $\endgroup$
    – user10001
    Sep 6 '12 at 22:28

Let's look for solutions of the PDEs in a form $\eta(x, t)= \eta(z)$ and $\xi(x, t)= \xi(z)$, where $z= x-c_T t$. If we substitute these solution to the PDEs, they are reduced to ODEs. But to answer you question, we only need the second equation, which has the form: $$ c_T^2 \eta_{zz} = {\lambda \over \rho_0} [\eta_{zz} ({\tau_0 \over \lambda} + \xi_z + {3 \over 2} (\eta_z)^2) + \eta_z \xi_{zz} ], $$ where index $z$ means derivative on $z$. Now, the first term in () on the right-hand side cancels with the left-hand-side term, because $\tau_0/\rho_0 = c_T^2$. The remaining terms are in fact the full derivative, therefore, we have: $$ [\eta_z + \xi_z + (\eta_z)^3/2]_z = 0, \quad \mbox{or} \quad \eta_z + \xi_z + (\eta_z)^3/2= C, $$ where C is a constant (does not depend on $z$). Since $\eta(z)$ has a pulse shape, then $\eta_z= 0$ at $z \to \pm \infty$. We assume also that $\xi_z= 0$ at $z \to \pm \infty$. Then $C=0$. So, finally we get that $$\xi_z= -\eta_z[1+(\eta_z)^2]. \qquad (*)$$ We know that $\eta(z)$ has a pulse shape. Therefore, it's derivative $\eta_z$ is zero at $z= -\infty$, then it decreases to some minimum, then it increases, crossing zero, goes to maximum and decreases again to zero at $z= +\infty$. Since exprssion in [ ] in Eq.(*) is always positive, $\xi_z$ has behavour similar to $\eta_z$, but with signs flipped. This means that $\xi(z)$ has also a pulse shape, but this pulse is flipped. I.e. if $\eta(z)$ is a hill-shaped, then $\xi(z)$ is a well-shaped.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.